Fracture resistance of endodontically treated teeth restored with indirect composite inlay and onlay restorations - An in vitro study - Ibraheem F. Alshiddi; Amjad Aljinbaz (Elsevier, 2016)
Objective: The purpose of this in vitro study was to evaluate and compare the fracture resistance and fracture mode of extensive indirect inlay and onlay composite resin restorations performed for endodontically treated premolars. Materials and methods: A total of 55 extracted maxillary premolars were randomly divided into four groups. The first group (n = 15) remained untreated to serve as a positive control; the second group (n = 15) was endodontically treated with inlay cavities prepared and restored with indirect composite inlay restorations; the third group (n = 15) was also endodontically treated with onlay cavities prepared and restored with indirect composite onlay restorations; and the fourth group (n = 10) was endodontically treated with mesio-occlusodistal (MOD) cavities prepared and left unrestored to serve as negative controls. Dual cure indirect composite resin was used to fabricate the inlay and onlay restorations performed for the second and third groups, respectively. All teeth were subjected to compressive axial loading test using a metal ball (6 mm in diameter) in a universal testing machine (Instron 1195) with a cross-head speed of 0.5 mm/min until a fracture occurred. Statistical analysis of fracture resistance and fracture mode were performed with analysis of variance (ANOVA) (α = 0.05) and Kruskal-Wallis (α = 0.05) tests, respectively. Results: For the four treatment groups, the mean fracture resistance values were 1326.9 N, 1500.1 N, 1006.1 N, and 702.7 N, respectively. Statistical analyses showed no significant differences between the mean fracture resistance of the intact tooth group and the inlay restoration group (p > 0.05), while significant differences were observed between the mean fracture resistance of all the other groups (p < 0.05). The Kruskal-Wallis test showed statistically significant differences between the fracture modes of the four groups. Conclusion: Within the limitations of this study, endodontically treated teeth were successfully restored with indirect composite inlay and onlay restorations. However, the fractures that accompanied the inlay restorations were more severe and were unable to be restored. Keywords: Fracture resistance, Composite, Inlay restoration, Onlay restoration, Endondontics